Al-Khabar Abadi, Muhammad Abu al-Laith. “The Methodology of Hadith Scholars (Muḥadithīn) in Dealing with Time and Place in the Sunnah,” Year 10, Issues 37-38 (Summer-Fall 1425 AH/ 2004 CE), Pp. 81-128. - آبادي محمد الخير (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2004)
In order to properly understand and apply the Sunnah, Muhammad al-Khabar calls for a selective review of the contents of hadith collections and analytically studying their interaction with the contemporary era and its elements, the society and its needs, and the individual and his or her capabilities. Al-Khabar attempts to establish a methodology to deal with the books of Sunnah in the framework of their various dimensions. His article focuses on one of these dimensions, that of time and place, which is considered one of the key factors in ascertaining the meaning of hadiths and thus understanding the Sunnah. His study is an attempt to establish guidelines for these dimensions of the Sunnah, inferred through the realities and incidences for which the Prophet Muhammad (ṢAAS) issued a ruling, changed a ruling, or preferred a ruling over another.